Fenologi Perubahan Warna Daun pada Terminalia catappa, Ficus glauca, dan Cassia fistula - Dibyanti Danniswari; Nizar Nasrullah; Bambang Sulistyantara (Jurnal Lanskap Indonesia, 2019)
Phenology refers to the study of seasonal appearances and timing of biological life-cycle events, such as flowering, leaf shedding, and leaf color changing. Landscapes could be enriched visually by employing these dynamic seasonal qualities in the design. Trees’ leaf color changing phenology is rarely considered in tree selection although it has a big potential to enhance a landscape’s aesthetics. To propose the right trees in the design, we need to understand when and how trees change. The objectives of this study were observing leaf color changing phenology of three tree species: Ficus glauca, Terminalia catappa, and Cassia fistula; comparing the results of chlorophyll content analysis and digital image analysis, and analyzing the correlation between chlorophyll content and climatic factors. The leaf color changing phenology was observed by two measurements, chlorophyll content and RGB (Red, Green, Blue) channel values. The lowest chlorophyll content in F. glauca and T. catappa was observed during the first weeks of January, while in C. fistula, was during the last weeks of December. F. glauca changed its leaf color from green to yellow right before leaf-shedding, T. catappa leaves changed from green to orange or red. C. fistula leaf color was shades of green. There were strong correlations between Red & Green values and chlorophyll content in F. glauca and T. catappa, but not in C. fistula. There was no climatic factor that had a significant correlation with the chlorophyll contents of any observed species. Future study is encouraged to cover the unobserved period and factors.Keywords: Cassia fistula, Ficus glauca, leaf color change, phenology, Terminalia catappa